Evidence of increasing sedentarism in Mexico City during the last decade: Sitting time prevalence, trends, and associations with obesity and diabetes - Medina, Catalina (PLoS One, 2017)
INTRODUCTION: Sedentary behaviors such as sitting time are associated with obesity and diabetes independently of total reported physical activity. This study aimed to describe the current sitting time/day prevalence and trends and to examine the association of sitting time with sociodemographic and clinical variables in Mexico City. METHODS: Two cross-sectional representative surveys in Mexico City were used for this analysis (2006: n = 1148 and 2015: n = 1329). Sedentary behavior questions from the International Physical Activity Questionnaire included time spent sitting on a weekday in the last week or on a Wednesday. Sitting time /day was divided into deciles, and participants in the highest decile (≥ 420 minutes/day) were classified within the high sitting category; others were classified in the low sitting time category. Multivariate logistic regression was used to evaluate the associations of sitting time with sociodemographic and clinical indicators, controlling for confounders and testing for potential interactions. RESULTS: A total of 13.7% (2006) and 14.8% (2015) adults were classified in the highest sitting time category (≥ 420 minutes/day). There was a significant increase in the average sitting time/day between the surveys (216.0 minutes in 2006 vs. 233.3 minutes in 2015, p < 0.001). In 2015, men, those aged 20–49 years, those in low-intensity jobs, students, and those with a high socioeconomic level were more likely to be in the highest sitting time category. Participants with overweight/obesity (OR = 2.37, 95% CI: 1.11, 5.09) and those with high glucose levels (survey finding) (OR = 2.34, 95% CI: 1.04, 5.25) were more likely to report sitting time in the highest category. DISCUSSION: Sitting time/day prevalence increased 8%, and average daily sitting minutes significantly increased by 8.2% (18 minutes) in the nine-year study period (2006–2015). Current public health policies should consider strategies not only for increasing physical activity levels, but also for reducing sitting time/day among the population as a measure to fight the growing epidemic of obesity and diabetes in Mexico.